Tripling the detection view of high-frequency linear-array-based photoacoustic computed tomography by using two planar acoustic reflectors - Li, Guo; Xia, Jun; Wang, Kun; Maslov, Konstantin; Anastasio, Mark A.; Wang, Lihong V. (Quantitative Imaging in Medicine and Surgery, 2014)
Background: Linear-array-based photoacoustic computed tomography (PACT) suffers from a limited view. Circular scanning does increase the detection view angle but is time-consuming. Therefore, it is desirable to increase the detection view angle of linear-array-based PACT without sacrificing imaging speed. Methods: Two planar acoustic reflectors placed at 120 degrees to each other were added to a lineararray- based PACT system. Each reflector redirects originally undetectable photoacoustic waves back to the transducer array elements, and together they triple the original detection view angle of the PACT system. Results: Adding two reflectors increased the detection view angle from 80 to 240 degrees. As a comparison, a single-reflector PACT has a detection view angle of only 160 degrees. A leaf skeleton phantom with a rich vascular network was imaged with the double-reflector PACT, and most of its features were recovered. Conclusions: The two acoustic reflectors triple the detection view angle of a linear-array-based PACT without compromising the original imaging speed. This nearly full-view detection capability produces higher-quality images than single-reflector PACT or conventional PACT without reflectors.